A tool to support the integration of noise control criteria in building design. Issue 2 (June 2016) - Şentop, Ayça; Bayazıt, Nurgün Tamer
This study describes an acoustic tool for architects and architecture students. The tool is intended to assist them in the determination of airborne sound insulation requirements and in the evaluation of building elements and their acoustic performance. The Building Elements Selection Tool has two parts: a catalogue and a calculator. The catalogue serves as a practical database of the sound insulation properties of various building elements, whereas the calculator is used for acoustic calculations. In this study, the usability of the tool has been tested by means of a validation task, in which a simple design problem was given to a group of architects, and the outcomes were then discussed.